บทบาทของขนาดหน้าต่างที่มีผลต่อการปรากฏสีของวัตถุในห้องทดสอบ - ห้าวเจริญ พฤฒพร; ห้าวเจริญ กฤตพร (Asian Creative Architecture, Art and Design, 2012)
บทคัดย่อ งานวิจัยนี้อาศัยแนวคิดการจดจำสภาพความสว่างของพื้นที่ที่มองเห็น (Recognized Visual Space of Illumination; RVSI) เพื่อใช้ศึกษาถึงผลของขนาดหน้าต่างต่อการปรากฏสีของแผ่นทดสอบภายใต้แสงสี โดยการปรากฏสีของแผ่นทดสอบที่อยู่ภายในห้องทดสอบ ซึ่งได้รับความสว่างจากแสงสี ได้แก่ แสงสีแดงที่ความอิ่มตัวแตกต่างกัน 3 ระดับ และแสงสีเหลืองที่ความอิ่มตัว 3 ระดับ และจะประเมินด้วยวิธีการบอกส่วนประกอบสีพื้นฐาน (elementary color naming method) โดยผู้สังเกตจะมองแผ่นทดสอบผ่านหน้าต่างขนาดต่างๆ จากห้องผู้สังเกต ซึ่งใช้หลอดฟลูออเรสเซนต์ชนิดเดไลท์ให้แสงสว่างไปยังแผ่นทดสอบ ผู้สังเกตที่ร่วมทำการทดลองมีทั้งหมดห้าคน ผลการทดลองพบว่า เมื่อมองแผ่นทดสอบผ่านหน้าต่างขนาดเล็กที่สามารถมองเห็นเฉพาะแผ่นทดสอบภายในช่องหน้าต่าง การปรากฏสีของแผ่นทดสอบจะอมไปทางสีของแสงที่ให้ความสว่างแก่ห้องทดสอบในขณะนั้น แต่เมื่อหน้าต่างมีขนาดใหญ่ขึ้นจนผู้สังเกตสามารถมองเห็นวัตถุอื่นๆ นอกเหนือจากแผ่นทดสอบภายในช่องหน้าต่าง การปรากฏสีของแผ่นทดสอบจะกลับไปคล้ายกับสีเดิมของแผ่นทดสอบนั้น แสดงให้เห็นว่าความคงที่ของสี (color constancy) เกิดขึ้นเมื่อผู้สังเกตสามารถสร้าง RVSI สำหรับห้องทดสอบได้ คำสำคัญ: การปรากฏสี, ความคงที่ของสี, ความสว่าง, การจดจำสภาพความสว่างของพื้นที่ที่มองเห็น Abstract This experiment is based on the concept of Recognized Visual Space of Illumination (RVSI) and aims to investigate the effect of window size on the color appearance of the test patch under colored illumination. The color appearance was judged by elementary color naming method for the test patch which was placed in a test room illuminated by colored illuminations, three red illuminations of different saturation and three yellow illuminations of different saturation. Subject observed the test patch from a subject room illuminated by fluorescent lamps of daylight type through window of various sizes. Five subjects participated in the experiment. We found that when the window was small so that only the test patch was seen within the window the color appearance of the test patch shifted into the direction of color of illumination, but when the window size was enlarged so that the subject could see some objects in the test room the color appearance returned to its original color. It’s implying that the color constancy hold when the subject can construct new RVSI for the test room. Keywords: Color Appearance, Color constancy, Illumination, Recognized Visual Space of Illumination (RVSI)